30. EVALUATION OF THE EFFECTIVEENESS OF HIGH FREQUENCY CHEST PERCUSSION MACHINE IN PATIENTS ON VENTILATORS AT INTENSIVE CARE DEPARTMENT 1, VIET DUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the effectiveness and adverse effects of the HFCWO high-frequency chest percussion machine on mechanically ventilated patients.Research methods: Prospective, clinical intervention, comparing 2 groups of mechanicallyventilated patients: group 1 received chest percussion with the HFCWO machine, group 2 received percussion by nurses.Results: Patients had an average age of 45.09 ± 18.3 years; BMI 21.98 ± 1.93 kg/m2; the main reason for hospitalization was traffic accidents (50%); the leading disease that required mechanical ventilation was central nervous system damage (42%).During the percussion process, group 1 had an increased respiratory rate and a slight decrease in SpO2 compared to before percussion. After sputum suction, the respiratory rate and SpO2 were no different from before intervention. Blood pressure and heart rate of group 1 patients did not change between before, during and after using the machine. Compared with group 2, group 1 had more sputum suctioning in the first 24 hours after intervention, shorter ventilation time and ICU stay, respiratory rate and rapid shallow breathing index were statistically significant. During the use of the machine, only 4% of patients sweated, there were no complications.Conclusion: HFCWO percussion machine is effective in eliminating airway secretions, improving respiratory symptoms, patients have less hemodynamic and respiratory changes.
Keywords: Percussion; percussion machine; respiratory physiotherapy